GEOCHEMICAL COMPONENT RELATIONSHIPS IN MORB FROM THE MID-ATLANTIC RIDGE, 22-35°N - Debaille V.; Doucelance R.; Schiano P.; Blichert-Toft J.; Agranier A.; Albarede F. (My University, 2006)
New trace element and Hf, Nd, and Pb isotope data are reported for 22 basalts collected between 22°N and 35°N on the Mid-Atlantic Ridge. (La/Sm)N ratios identify the presence of enriched (E)-MORB in the northernmost part of this area and normal (N)-MORB elsewhere. A negative correlation is observed when 143Nd/ 144Nd is plotted against 206Pb/204Pb, 207Pb/204Pb, and 208Pb/ 204Pb, whereas 176Hf/177Hf appears not to correlate with any of the other isotopic ratios. The E-MORB samples are characterized by high 206Pb/204Pb, 207Pb/204Pb, 208Pb/204Pb, and low 143Nd/144Nd. Principal Component Analysis (PCA) of Pb isotopes alone identifies three, and only three, significant geochemical end-members ('components'). Including Nd and Hf isotopic data in the PCA produces spurious components, partly because of curved mixing relationships, and partly because of fractionation during melting. Our preferred interpretation of why 176Hf/ 177Hf is decoupled from the other isotopic ratios is, as inferred from recent experimental data, that the Hf isotopic compositions of the melt and the residue fail to equilibrate during melting. A strong correlation between (Sr/Nd)N and (Eu/Eu*)N indicates that plagioclase is a residual phase of N-MORB, but not of E-MORB melting. The three end-members identified in this study are the depleted mantle, a common-type component, and an enriched plume-type end-member. The common, or 'C'-type, end-member is characteristic of E-MORB and may itself be a mixture containing recycled oceanic crust (the MORB suite, terrigenous sediments, and/or oceanic plateaus). The plume-type end-member is likely to represent the lower mantle and may involve some primordial material. It is shown that mantle isochrons in general and the Pb-Pb isochron in particular do not characterize a specific geodynamic process acting to create mantle heterogeneities. © 2005 Elsevier B.V. All rights reserved.
Keywords: DISEQUILIBRIUM MELTING; E-MORB; HF ISOTOPES; MANTLE END-MEMBERS; MID-ATLANTIC RIDGE; N-MORB; ND ISOTOPES; PB ISOTOPES; PLAGIOCLASE; PRINCIPAL COMPONENT ANALYSIS